[Apoptosis induced by free fatty acids]. - Eitel, K; Staiger, H; Brendel, MD; Brandhorst, H; Bretzel, R; Häring, H; Kellerer, M (2003)
BACKGROUND AND AIMS: Elevated free fatty acid (FFA) levels are believed to be one of the major contributing factors in the pathogenesis of type 2 diabetes. FFAs enhance peripheral insulin resistance, promote beta-cell dysfunction, and trigger beta-cell death. The purpose of this study was to investigate whether the lipoapoptotic effect of FFAs is determined by the degree of saturation and the chain length, and which pathways might be involved. MATERIAL AND METHODS: After incubation of RIN1046-38 rat insulinoma cells and primary human islet cells with different FFAs, apoptosis was assessed by flow cytometry (sub-G1-DNA formation) and TUNEL assay, respectively. Intracellular distribution of protein kinase C-delta (PKC-delta) was determined by confocal laser microscopy. RESULTS: In RIN1046-38 cells, the sub-G1 fraction increased 40-fold over basal (0.5% to approximately 20%) after treatment with the saturated FFAs palmitate and stearate (1 mM, 24 h), while the monounsaturated FFAs palmitoleate and oleate as well as the polyunsaturated FFA linoleate had no proapoptotic effect. Unsaturated FFAs even more prevented palmitate- and stearate-induced apoptosis completely. Furthermore, these results could be confirmed in primary beta-cells of human islets. Investigating potential underlying signaling pathways, it was found that only the saturated FFAs were able to induce nuclear translocation of PKC-delta. CONCLUSIONS: FFAs exert different effects on beta-cell survival. Saturated FFAs turned out to be pro-apoptotic, whereas unsaturated FFAs protected from saturated FFA-induced apoptosis. Furthermore, our data suggest an involvement of PKC-delta in apoptosis induced by saturated FFAs.